An Analysis of The Effectiveness of Word Attack Strategy in Boosting Students’ Reading Comprehension in Indonesian Secondary School - Sarmila, Sarmila; Rahmaeni, Rahmaeni; Hasan, Hasan (EduPsyCouns: Journal of Education, Psychology and Counseling, 2025)
The research was aimed at determining how was application of word attack strategy impacts on students' reading comprehension skills in class VIII SMP Negeri 2 Enrekang. The background of this research was based on the preliminary observation which showed that many students had difficulty in understanding English reading texts. This was due to limited vocabulary and less effective learning approaches to help students read better. This research applied quasi-experimental method with pretest-posttest control group design. The populations of the research were all VIII grade students of SMP Negeri 2 Enrekang. The sampling was taken by simple random sampling technique. Based on the pretest results, the mean value was 47 for the experimental group and 40 for the control group. After giving treatment in the form of applying the Word Attack strategy, the mean value of the experimental group increased to 80, while the control group increased to 53. To test the hypothesis, the data were analyzed using an independent sample t-test. The result showed significance value of 0.000, which indicated that the Word Attack strategy had a significant effects on the students’ reading ability of grade VIII at SMP Negeri 2 Enrekang. It is therefore, it could be determined that the Word Attack strategy was effective in enhancing students' reading ability.